The Use of Tree Diagram Technique in Teaching Vocabulary - Wa Risna Wati; Raisa Anakotta; Doni Sudibyo (INTERACTION: Jurnal Pendidikan Bahasa, 2020)
The objective of this research is to find out whether a tree diagram technique is effective or not in teaching vocabulary at seventh grade in MTs Muhammadiyah 2 Aimas. Related to the objective of the research used pre- experimental quantitative research design. The design of this research is one group pretest- posttest. The population of this research was seventh grade students divide two classes that were VII A and VII B and the total them are 24 students. Based on purposive sampling, the researcher chosed seventh B grade and which total are 18 students because the class is lack of vocabulary so the low score. In the collecting the data, the researcher used 20 items multiple choice for pretest and posttest. In analyzed the data, the researcher used SPSS 20 program to calculation the data.The result finding of the research showed that the result of N-gain is (58.46) or (58%) the categorized was quiet effective. In addition to result of T-test is P value (0.000) < α (0.05), it means that H0 was rejected and Ha was accepted. The alternative hyphothesis (Ha) was there is an effective in teaching vocabulary using tree diagram between pretest and posttest. And also , it can be seen from the mean score from the posttest was (45.83) improved on posstest ( 77.50). It can be concluded that tree diagram technique in teaching vocabulary were effective in teaching vocabulary.